HYPOTHYROIDISM IN AYURVEDA - A CONCEPTUAL STUDY (AYUSHDHARA, 2015)
Hypothyroidism is a clinical syndrome resulting from insufficient production of thyroid hormones, which is a common endocrinal disorder seen all over the world. It affects the metabolism of the body even at cellular level and can affect any organ virtually. The incidence of hypothyroidism is rising rapidly. It is estimated to have affected 2-5% of global population. It is more prevalent among females. The symptoms of hypothyroidism are notorious for their non specific nature and for the way in which they mimic symptoms of other systemic diseases. It leads to a long life of pathological events and makes the affected person to remain dependent on hormonal replacement throughout his life.Thus, there is an increasing demand to understand the disease in view of Ayurveda and to establish the management through Ayurvedic system of medicine. On reviewing the clinical presentation from all classical texts it is found that in hypothyroidism there is abnormality of Jatharagni and Dhatwagni along with abnormality of Kapha and Vata Dosha as well as Rasavaha, Raktavaha, Medovaha, Sukravaha and Manovaha Srotases. Dosha-dushyasamoorchhana in various Dhatus results in the systemic manifestation of the disease. Thus, the line of treatment involves Deepana, Pachana, Srotoshodhana and Kapha vata shamana.